Poetry in the 20th Century Jambi Seberang Community Islamic Education - Nirwan Il Yasin; Siti Syuhada (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
Researchers and academics have indeed done a lot of research in Jambi. Aspects of the life side of the people of Jambi opposite in any study have been carried out. One of them is historical studies. The research process was also carried out by involving in-depth studies which became a reference to previous reviews of this research. Poetry in the learning process of Jambi education in the area across from Jambi City that still needs to be revealed. This awareness also wants to be built in the midst of many educational patterns that have been adapted to the times. Poetry in the 20th century became a powerful method, besides that in general the people of Jambi already knew the treasures of this poetry as part of the cultural speech of their people. One of the Tuan Guru who uses poetry in his learning is Tuan Guru Abdul Qodir Ibrahim. In the research using historical science methods, namely: heuristics, criticism, interpretation, and historiography. This disclosure was made so that all forms of educational change processes that exist in the Jambi community can be appointed as the identity of the Jambi people. This disclosure was carried out in the Jambi Seberang area which was the first area of ??Islamic education in Jambi. This research attempts to explain poetry in Islamic education for the people of Jambi, and the dynamics of its development process. Keywords: Poetry, Methods of Islamic Education, Tuan Guru Abdul Qodir Ibrahim